Turismo de base comunitária como indutor de desenvolvimento local: um estudo da realidade e potencialidades no distrito de Porto Salvo, município de Vigia de Nazaré-PA - DORES, Liliane Amanda Oliveira das (Universidade Federal do Pará, 2017)
This study deals with community-based tourism and local development inductor, consisting in an analysis of the reality and potential in the Porto Salvo District, Vigia de Nazaré municipality. It is proposed to identify the potential to develop community-based tourism, assessing to what extent the local situation allows community inclusion in the management of local tourism resources. In this sense, it proved to be the resources available in the district; He identified himself and was organized systematically the factors that hinder the development of community-based tourism in the study area; It is possible to identify and map the main attractions highlighted by community featuring them and proposing activities to be undertaken in order to enhance its use in community benefit. As a methodological resource used a qualitative approach and criticizes the procedures and processing of data, it also adopted, bibliographic and documentary research, interviews targeted public sectors related to tourism, community leaders and older residents. The review was based on the principles of sustainability, taking into account two central pillars: the local tourism (primary and secondary structure, tourism) and political-institutional. The survey results show that the district of Porto Salvo has potential for development of Tourism Community Based, given that it is rich in natural and cultural resources, has a historical importance in the municipal formation, the population lives under the their habits and customs and value their identity. The community of joint participation was found in organizing local events and achievements, and also in the search for community interests. The role of universities, ONGs was also identified, through projects and courses offered in communities. Despite the difficulties encountered as the lack of local policies and targeted plans to the district, lack of awareness in relation to tourism, preservation of natural resources, inadequate basic infrastructure, equipment and means of support for the unsatisfactory tour, it is believed that these difficulties can be overcome by a commitment from both the public sector and the community through a joint and participatory planning, involving concrete actions directed to the district.